The Khmers of Cambodia the story of a mysterious people - Edmonds, I. G (Indianapolis Bobbs-Merrill, 1970)
Describes the geography, history, culture, people, and present-day political situation of Cambodia.
Bibliography: p. 154
1
Keywords: Khmers -- History; Cambodia -- Civilization